Prevalence of metabolic syndrome in stroke patients: a prospective multicenter study in Japan - Takahashi, Takeshi; Harada, Masahiro; Kikuno, Takaaki; Ujihara, Makoto; Sadamitsu, Daikai; Manabe, Yasuhiro; Yasaka, Masahiro; Takayama, Hayato; Kobori, Shozo; Araki, Eiichi (Acute Medicine & Surgery, 2014)
Aims The fact that Metabolic Syndrome (MetS) increases the risk of atherosclerosis has been epidemiologically studied and proven; however, a prospective study on the prevalence of MetS in stroke patients has never been conducted because of the difficulty in diagnosis under critical illness in the acute phase. Therefore, we conducted a prospective multicenter study to investigate the prevalence of MetS in stroke patients with modified diagnostic criteria for MetS. Methods Stroke patients admitted in the seven participating Emergency and Critical Care Centers within the two years from April 2007 were registered in this study as a prospective multicenter study. Inclusion criteria were 50 to 89 year‐old stroke patients who presented within three days from the onset of symptoms. A total of 992 subjects were classified according to the stroke type and the prevalence of MetS and the associated risk factors were investigated. The participants in a medical checkup without any history of a stroke were enrolled as the control group, and compared between the two groups. Results The prevalence of MetS as well as hyperglycemia and dyslipidemia in the infarction group was significantly higher than that in the non‐stroke group. While the hemorrhage group showed no significant difference in the prevalence of MetS, only hypertension was significantly high. According to a subtype analysis, there is a significant correlation between waist circumference increment of the stroke patients and the prevalence of the risk factors of hypertension, hyperglycemia and dyslipidemia. Conclusions Different risk factors are significantly related to the type of stroke.